2019
DOI: 10.3389/fbioe.2019.00355
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Osteogenic Differentiation of Induced Pluripotent Stem Cells (iPSCs) Using Bioactive Glasses: An in vitro Study

Abstract: Selection and use of an optimal cell source for bone tissue engineering (BTE) remain a challenging issue; the invention of induced pluripotent stem cells (iPSCs) have created new hopes on this regard. At the present study, we attempted to show the usability of iPSCs in combination with bioactive glasses (BGs) for bone regeneration applications. For this aim, iPSCs were cultured and incubated with the strontium and cobalt-containing BGs for different intervals (1, 5, and 7 days). The cell cytotoxicity and attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The same glass compositional systems with particle size below 38 µm were also tested using induced pluripotent stem cells (iPSCs), which offer great promises for osseous repair and regeneration that cannot be achieved with other cell sources (e.g., embryonic stem cells), including the absence of ethical issues, the lack of immune rejection as well as the ability to differentiate into osteogenic cells [76]. Although incubation of iPSCs with such glasses resulted in a significant reduction of cell viability over 7 days because of cell apoptosis, the data obtained from ALP activity assay and gene expression revealed that the iPSCs could adhere and spread onto the glass particles and over-express the osteogenic markers, including osteocalcin, osteonectin and Runx2 [77]. The same glass compositions were eventually tested in vivo: after being seeded with HUVECs, glass granules in the range of 100 to 1000 µm were implanted in critical size defects of distal femur in rabbits and, according to histologic and immune-histologic results, bone healing was better in the group receiving Sr/Co-codoped glass constructs in comparison with the Co-free groups at both 4 and 12 weeks of follow-up (Figure 5) [78].…”
Section: Bone-contact Fieldmentioning
confidence: 99%
“…The same glass compositional systems with particle size below 38 µm were also tested using induced pluripotent stem cells (iPSCs), which offer great promises for osseous repair and regeneration that cannot be achieved with other cell sources (e.g., embryonic stem cells), including the absence of ethical issues, the lack of immune rejection as well as the ability to differentiate into osteogenic cells [76]. Although incubation of iPSCs with such glasses resulted in a significant reduction of cell viability over 7 days because of cell apoptosis, the data obtained from ALP activity assay and gene expression revealed that the iPSCs could adhere and spread onto the glass particles and over-express the osteogenic markers, including osteocalcin, osteonectin and Runx2 [77]. The same glass compositions were eventually tested in vivo: after being seeded with HUVECs, glass granules in the range of 100 to 1000 µm were implanted in critical size defects of distal femur in rabbits and, according to histologic and immune-histologic results, bone healing was better in the group receiving Sr/Co-codoped glass constructs in comparison with the Co-free groups at both 4 and 12 weeks of follow-up (Figure 5) [78].…”
Section: Bone-contact Fieldmentioning
confidence: 99%
“…iPSC-derived MSCs on hydroxyapatite-coated polymer scaffolds induce the osteoclastic differentiation of iPSC-macrophage (by NFATC1, CATK, CTR, and TRAP5b) and possess stronger osteogenic activity of human iPSCs compared to low HA or PLLA/PLGA alone [142]. Bioglass induces the stimulation of osteogenesis of iPSCs in vitro, which was assayed by ALP levels and real-time PCR [143]. The osteogenic differentiation of iPSCs from human gingival fibroblasts was notably increased when admixed with nanohydroxyapatite/chitosan/gelatine 3D scaffolds [144].…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…In addition, cell viability is an important parameter that must be considered during the evaluation of novel materials for the treatment of bone defects. Several established assays are frequently used for this purpose, including the colorimetric MTT, MTS and water-soluble tetrazolium (WST) assays, as well as fluorometric assays like calcein-AM and fluorescein–diacetate (FDA) staining [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%